SYNERGISTIC EFFECTS OF AGRO-INDUSTRIAL WASTES ON ALPHA AMYLASE PRODUCTION BY BACILLUS AMYLOLIQUEFACIENS IN SEMI SOLID SUBSTRATE FERMENTATION - Yaras, Ali; Selen, Veyis; Ozer, Dursun (Pamukkale Univ, 2015)
This study concerns with the combinations of soybean meal (SM), wheat bran (WB) and whey were utilized as the substrates for alpha-amylase production by Bacillus amyloliquefaciens NRRL B-645. As a result of the experiments, the highest a-amylase activity (4257 U/ml) was obtained containing SM 20 g/l, WB 5 g/l, whey 5% (v/v), peptone 1 g/l, yeast extract (YE) 0.5 g/l and (NH4)(2)SO4 1 g/l at 33 degrees C and 150 rpm for 48 h. This innovative process for the alpha-amylase production can be extended to different enzymes using various agro-industrial wastes.
Keywords: Alpha amylase; Bacillus amyloliquefaciens NRRL B-645; Agro-industrial wastes; Semi solid substrate fermentation